2008
DOI: 10.1111/j.1467-6494.2008.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Egos Inflating Over Time: A Cross‐Temporal Meta‐Analysis of the Narcissistic Personality Inventory

Abstract: A cross-temporal meta-analysis found that narcissism levels have risen over the generations in 85 samples of American college students who completed the 40-item forced-choice Narcissistic Personality Inventory (NPI) between 1979 and 2006 (total n=16,475). Mean narcissism scores were significantly correlated with year of data collection when weighted by sample size (beta=.53, p<.001). Since 1982, NPI scores have increased 0.33 standard deviation. Thus, almost two-thirds of recent college students are above the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
584
10
35

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 761 publications
(676 citation statements)
references
References 94 publications
30
584
10
35
Order By: Relevance
“…Men's scores were not significantly correlated with the year of data collection (β = −.19, p > .05). Contradictory to previous research findings (Twenge et al, 2008), we also found that women's scores were not positively related to the year of data collection (β = −.18, p > .05), failing to support Hypothesis 2b. Figure 2 displays male and female college students' mean scores on the NPI from 1990 to 2013.…”
Section: Generational Cohort Effectcontrasting
confidence: 99%
See 2 more Smart Citations
“…Men's scores were not significantly correlated with the year of data collection (β = −.19, p > .05). Contradictory to previous research findings (Twenge et al, 2008), we also found that women's scores were not positively related to the year of data collection (β = −.18, p > .05), failing to support Hypothesis 2b. Figure 2 displays male and female college students' mean scores on the NPI from 1990 to 2013.…”
Section: Generational Cohort Effectcontrasting
confidence: 99%
“…By contrast, all of the other previously mentioned studies on women's changing agentic characteristics over time covered considerably longer time spans than that available for narcissism; that is, Eagly and Karau (1991) extended back to 1956; Konrad et al (2000) extended back to 1972; Leaper andAyres (2007) extended back to 1962;Su et al (2009Su et al ( ) extended back to 1965Twenge (1997Twenge ( ) extended back to 1973and Twenge (2001) extended back to 1931. Twenge, Konrath, Foster, Campbell, and Bushman (2008) briefly discussed changes in the narcissism gender difference over time in the context of a meta-analysis focused on "generation me" or increases in undergraduates' narcissism over time. Although their narcissism data (for their gender difference subanalyses) only went back to 1992, they found indications that undergraduate men scored higher in narcissism than did undergraduate women and that the mean difference decreased over time.…”
Section: Women's Change In Narcissism Over Timementioning
confidence: 99%
See 1 more Smart Citation
“…Additional core personality traits of Millennials include sheltered, confident, conventional, and pressured (Strauss and Howe 2000). Millennials are also regarded as self-centered, unmotivated, disrespectful, and disloyal Strauss 2003, Myers andSadaghiani 2010); in fact, Millennials are characterized as significantly more narcissistic than older generations (Twenge et al 2008). …”
Section: Characteristics Of the Millennial Generationmentioning
confidence: 99%
“…New technology as both a cause and solution for declining empathy Over the past several decades, there have been documented declines in face-to-face social interactions, and in young people's self-perceived ability to care and connect with others (Konrath, Chopik, Hsing, & O'Brien, 2014;Konrath, et al, 2011;O'Brien, Konrath, Grühn, & Hagen, 2013;Putnam, 2000;Twenge, Konrath, Foster, Campbell, & Bushman, 2008). For example, our research has found that the personality trait narcissism has risen since the early 1980s among American college students , while dispositional empathic concern and perspective taking have simultaneously been declining (Konrath, et al, 2011).…”
Section: The Malleability Of Empathymentioning
confidence: 99%